The Application of Microwave Technology in Demulsification of Water-in-Oil Emulsion for Missan Oil Fields - A.M. Mohammed, Sawsan; S. Mohammed, Mortatha (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
A series of batch demulsification runs were carried out to evaluate the final emulsified water content of emulsion samples after the exposure to microwave. An experimental study was conducted to evaluate the effects of a set of operating variables on the demulsification performance. Several microwave irradiation demulsification runs were carried out at different irradiation powers (700, 800, and 900 watt), using water-in-oil emulsion samples containing different water contents (20-80%, 30-70%, and 50-50%) and salt contents (10000, 20000, and 30000 ppm). It was found that the best separation efficiency was obtained at 900watt, 50% water content and 160 s of irradiation time. Experimental results showed that microwave radiation method can enhance the demulsification of water -in- oil emulsions in very short time compared to the conventional methods.